Binuclear trans‐Bis(β‐iminoaryloxy)palladium(II) Complexes Doubly Linked with Pentamethylene Spacers: Structure‐Dependent Flapping Motion and Heterochiral Association Behavior of the Clothespin‐Shaped Molecules. Issue 23 (17th April 2014) - Naito, Masaya; Souda, Hiroyuki; Koori, Hiroshi; Komiya, Naruyoshi; Naota, Takeshi
Abstract The synthesis, structure, and solution‐state behavior of clothespin‐shaped binuclear trans‐bis(β‐iminoaryloxy)palladium(II) complexes doubly linked with pentamethylene spacers are described. Achiral syn and racemic anti isomers of complexes 1–3 were prepared by treating Pd(OAc)2 with the corresponding N, N′‐bis(β‐hydroxyarylmethylene)‐1, 5‐pentanediamine and then subjecting the mixture to chromatographic separation. Optically pure (100 % ee) complexes, (+)‐anti‐1, (+)‐anti‐2, and (+)‐anti‐3, were obtained from the racemic mixture by employing a preparative HPLC system with a chiral column. The trans coordination and clothespin‐shaped structures with syn and anti conformations of these complexes have been unequivocally established by X‐ray diffraction studies. 1H NMR analysis showed that (±)‐anti‐1, (±)‐anti‐2, syn‐2, and (±)‐anti‐3 display a flapping motion by consecutive stacking association/dissociation between cofacial coordination planes in [D8]toluene, whereas syn‐1 and syn‐3 are static under the same conditions. The activation parameters for the flapping motion (ΔH≠ and ΔS≠) were determined from variable‐temperature NMR analyses as 50.4 kJ mol−1 and 60.1 J mol−1 K−1 for (±)‐anti‐1, 31.0 kJ mol−1 and −22.7 J mol−1 K−1 for (±)‐anti‐2, 29.6 kJ mol−1 and −57.7 J mol−1 K−1 for syn‐2, and 35.0 kJ mol−1 and 0.5 J mol−1 K−1 for (±)‐anti‐3, respectively. The molecular structure and kinetic parameters demonstrate that all of the anti complexes flap with a twisting motion in [D8]toluene, although (±)‐anti‐1 bearing dilated Z‐shaped blades moves more dynamically than I‐shaped (±)‐anti‐2 or the smaller (±)‐anti‐3. Highly symmetrical syn‐2 displays a much more static flapping motion, that is, in a see‐saw‐like manner. In CDCl3, (±)‐anti‐1 exhibits an extraordinary upfield shift of the 1H NMR signals with increasing concentration, whereas solutions of (+)‐anti‐1 and the other syn/anti analogues 2 and 3 exhibit negligible or slight changes in the chemical shifts under the same conditions, which indicates that anti‐1 undergoes a specific heterochiral association in the solution state. Equilibrium constants for the dimerizations of (±)‐ and (+)‐anti‐1 in CDCl3 at 293 K were estimated by curve‐fitting analysis of the 1H NMR chemical shift dependences on concentration as 26 M−1 [KD(racemic)] and 3.2 M−1 [KD(homo)], respectively. The heterochiral association constant [KD(hetero)] was estimated as 98 M−1, based on the relationship KD(racemic)=1/2 KD(homo)+1/4 KD(hetero). An inward stacking motif of interpenetrative dimer association is postulated as the mechanistic rationale for this rare case of heterochiral association.